Beyond the usual suspects: emerging uropathogens in the microbiome age - Moreland, Robert B.; Choi, Brian I.; Geaman, Wilson; Gonzalez, Caroline; Hochstedler-Kramer, Baylie R.; John, Jerrin; Kaindl, Jacob; Kesav, Nikita; Lamichhane, Jyoti; Lucio, Luke; Saxena, Malika; Sharma, Aditi; et al. (Frontiers in Urology, 2023)
The advent of sensitive enhanced culture (metaculturomic) and culture-independent DNA-based (metagenomic) methods has revealed a rich collection of microbial species that inhabit the human urinary tract. Known as the urinary microbiome, this community of microbes consists of hundreds of distinct species that range across the entire phylogenetic spectrum. This new knowledge clashes with standard clinical microbiology laboratory methods, established more than 60 years ago, that focus attention on a relatively small subset of universally acknowledged uropathogens. Increasing reports support the hypothesis that this focus is too narrow. Single uropathogen reports are common in women with recurrent urinary tract infection (UTI), although wider disruption of their urinary microbiome is likely.Typical "UTI" symptoms occur in patients with "no growth" reported from standard culture and sometimes antibiotics improve these symptoms. Metaculturomic and metagenomic methods have repeatedly detected fastidious, slow growing, and/or anaerobic microbes that are not detected by the standard test in urine samples of patients with lower urinary tract symptoms. Many of these microbes are also detected in serious non-urinary tract infections, providing evidence that they can be opportunistic pathogens. In this review, we present a set of poorly understood, emerging, and suspected uropathogens. The goal is to stimulate research into the biology of these microbes with a focus on their life as commensals and their transition into pathogens.